THE PROBLEM OF MENTALITY IN THE HUMANITIES: BASIC APPROACHES - E. A. Magomedov; Yu. G. Yusupov (Юг России: экология, развитие)
In this article mentality is considered as the object of humanitarian sciences. Taking into account a lot of definitions of mentality existing nowadays, the main approaches to the studing this phenomenon are indicated in this article. The most spread classifications of the definitions of this term is also given in this article.